Análise de estaqueamento pelo método das cargas limite - Cabral, David Antunes (1982)
We first present a discussion on safety factors and piling design using the elasticity theory. We analyse thereafter the possible types of pile failure and develop studies which allow us to apply the elastic-plastic method to piling design. We may obtain then a redistribution of the load of the most highly loaded piles to the others, according to the pile group characteristics and to the load-settlement curve of each pile. The main objectives of the present thesis are a better utilization of piles, increasing the savings in foundation and the calculation of the rupture of the pile group submitted to an initial service loading and then to an incremental loading according to the type of rupture to be analysed. As an application of the method, we have developed a computer program and calculated some examples.